PENGARUH POLA PENYAJIAN END OF SEQUENCE (EoS) DAN SERI INFORMASI PENDEK DALAM PENGAMBILAN KEPUTUSAN INVESTASI - Nirwana Putri Pravitasari; Luciana Spica Almilia (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
This study tested the model of belief adjustment in investment decision The purpose of this study was to reexamine whether there are differences in investment decisions between participants were informed of good news followed by bad news than participants who obtain information about bad news followed by good news on the pattern of presentation End of Sequence and series of short information. Design of Experiments in this study is that the pattern of presentation 1x1x2 End Of Sequence, series of short information and directions evidence (good news followed by bad news and the bad news followed by good news). The research hypothesis of research in this study were tested by Mann Whitney test. Variables used in this research is an investment decision, patterns of presentation end of the sequence, a series of short information, and order of proof. Participants involved in this research were 44 students Perbanas Surabaya bachelor degree majoring in Accounting or Management that are being or have taken courses of Financial Statement Analysis and Investment Management and Capital Markets. The result obtained is that there are significant differences in the final judgment participants who received information of good news followed by bad news compared to participants who received information about bad newsfollowedby good news also recency effect occurs in making investment decisions.Keywords: End Of Sequence, Investment Decision, Recency Effect,